2014
DOI: 10.1038/bjc.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitors use is associated with reduced risk of esophageal adenocarcinoma in patients with Barrett’s esophagus: a meta-analysis

Abstract: Background:Esophageal adenocarcinoma (EAC) has high mortality and is increasing in incidence. Barrett's esophagus (BE) increases the risk for EAC. Studies have reported inconsistent findings on the association between use of cyclooxygenase (COX) inhibitors and the risk of neoplastic progression in BE patients. Therefore, we performed a meta-analysis to investigate this association.Methods:A meta-analysis was undertaken among a total of 9 observational studies using fixed- and random-effects models, comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 48 publications
0
42
1
Order By: Relevance
“…No signifi cant eff ect was shown for H 2 RA usage in two studies ( 57 ). In another meta-analysis of 9 observational studies of 5,446 participants (605 with HGD or EAC), usage of cyclooxygenase inhibitors, aspirin, and nonaspirin cyclooxygenase inhibitors was associated with reduced risk for HGD and EAC independent of duration of therapy ( 58 ). By means of their antiproliferative, proapoptotic, antiangiogenic, and immunomodulatory eff ects, statins may prevent cancer development and growth.…”
Section: Summary Of Evidencementioning
confidence: 98%
“…No signifi cant eff ect was shown for H 2 RA usage in two studies ( 57 ). In another meta-analysis of 9 observational studies of 5,446 participants (605 with HGD or EAC), usage of cyclooxygenase inhibitors, aspirin, and nonaspirin cyclooxygenase inhibitors was associated with reduced risk for HGD and EAC independent of duration of therapy ( 58 ). By means of their antiproliferative, proapoptotic, antiangiogenic, and immunomodulatory eff ects, statins may prevent cancer development and growth.…”
Section: Summary Of Evidencementioning
confidence: 98%
“…A recently published meta-analysis showed that, overall, COX inhibitor use was associated with a reduced risk of OAC/HGD among patients with BO (RR 0.64, 95% CI 0.53 to 0.77). Both aspirin and non-aspirin COX inhibitors reduced the risk of OAC/HGD (RR 0.63, 95% CI 0.43 to 0.94 and RR 0.50, 95% CI 0.32 to 0.78, respectively) 192. However, the risk/benefit ratio of aspirin and NSAIDs is unclear, given the risk of GI bleeding and haemorrhagic stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally statins inhibit proliferation and induce apoptosis in Barrett's cell lines and these effects are enhanced in an additive manner in combination with inhibition of the cyclo-oxygenase-2 pathway (10,11). Over-expression of COX-2 in Barrett's mucosa has been reported, and experimentally (34), and in clinical studies beneficial effects of COX-inhibitors on progression to cancer have been reported (13,16,(35)(36)(37). Thus it is possible that statin and aspirin impair survival of the Barrett's clone at a very early stage and so impair establishment of a mature Barrett's segment.…”
Section: Discussionmentioning
confidence: 99%